Toxic properties of holothurian’s triterpene glycosides - D. L. Aminin; V. I. Kalinin (Вестник войск РХБ защиты)
Holothurians (or sea cucumbers) are echinoderms and are found in all areas of the world oceans. These animals produce special low-molecular metabolites - triterpene glycosides, which are a means of chemical protection of holothurians from predators. The content of triterpene glycosides in the tissues of holothurians can reach a significant amount of up to 1 g/kg, and especially many of these compounds are localized in the Cuvierian tubules - special protection organ presents in a number of tropical holothurians. Tritirepene glycosides of holothurians are quite toxic, they exhibit hemolytic, cytotoxic and neurotoxic activity at a concentration range of 1×104–1×106 M. The toxic properties of glycosides are based on the ability of these compounds to interact with ∆5-sterols (mainly cholesterol) of plasma membranes and form ion-conducting complexes. In turn, this leads to a change in the ion permeability and selectivity of biomembranes, disruption of barrier properties, ion homeostasis and osmolarity of cells, and further to cell lysis and death.Contact with holoturias when diving in shallow water, which is fraught with damage to the eyes and mucous membranes by triterpene glycosides, may be of some danger to humans. Excessive consumption of commercial edible holothurians in food, especially without prior heat treatment, as is customary in some South-East Asia countries, can lead to diarrhea and dyspepsia. Triterpene glycosides in the bloodstream can lead to blood lysis and serious consequences up to death.The holothurians are animals commercially harvested in Russia. They are used in food and for the preparation of medicinal supplements and preparations. Excessive consumption of commercial edible holothurians for food, especially without long-term boiling, as is customary in Southeast Asia, can lead to diarrhea and dyspepsia. Triterpene glycosides in the bloodstream can lead to blood lysis and serious consequences up to death. The use of dietary supplements with an uncontrolled glycoside content is fraught with similar consequences, and the presence of immunosuppressants among glycosides that have fallen into such additives and drugs can worsen the condition of patients or sick animals. Control of the qualitative and quantitative content of glycosides in food and medicinal products from holothurians should be an integral part of measures to improve the biological safety of citizens of the Russian Federation.